La simpatetica compassione tra pietà e benevolenza - Iaia, Gaetano (Bollettino Filosofico, 2022)
In Schopenhauer’s philosophy, compassion is both the direct source of ethical practice, and the foundation of ethics as science. In this sense, compassion is not merely an affection opposed to or coinciding with reason, nor does the ethics of compassion dispense with any form of rational self-determination. Schopenhauer’s ethics is not normative, but descriptive and axiological, as in the human “will” the compassion, although as such it is not action, transforms (or can transform) the moral imperative into directives relevant to action. In this paper we intend to focus on the Schopenhauerian concept of compassion by examining, through it, the logic adopted by the philosopher in order to establish it as the foundation of ethics, highlighting at the same time some difficulties which may result from this. Keywords: Compassion, Egoism, Ethics, Mitleid, Schopenhauer